Effects of light on sleep in older adults: a scoping review. Issue 1 (29th November 2022) - Jiang, Lei; Zhou, Baibing; Han, Han
Abstract: In light of the increase of aging populations, there is a need to focus on how older adults experience sleep disorders. This scoping review aimed to synthesize the features of the light and its effects on sleep in older adults. A total of 25 articles focusing on the effects of light on sleep among older adults were included. We synthesized light intensity, treatment duration, and the spectrum of light therapy as well as features of natural and artificial light that were used to improve sleep outcomes. Literature has shown evidence for the positive effects of light therapy on sleep in older adults. Older adults are, therefore, encouraged to receive frequent sunlight exposure and artificial lighting that accords with the cycle of their circadian rhythms.